Experimental in-plane evaluation of light timber walls panels - Branco, Jorge M. (2017)
In general, the satisfactory seismic performance of timber buildings can be partially attributed to the material characteristics of the wood itself and to the lightness of its own structure. The aim of this paper is to analyze the in-plane behavior of light timber walls panels through a series of monotonic and cyclic tests, and to evaluate how the sheathing material and the fixation to the base influence the overall response of the wall. Five tests are presented and discussed while the reliability of an analytical method to predict the response of the walls is studied. The sheathing material revealed to be important in the overall response of the wall. Moreover, the type of fixation to the base also revealed to be important in the in-plane response of timber walls. In-plane stiffnesses, static ductility, energy dissipation and damping ratio have been quantified.